INDEKS GLIKEMIK DAN BEBAN GLIKEMIK TEMPE DENGAN SUBSTITUSI BIJI LABU KUNING (Cucurbita moschata) - Thalia Oktaviani Pradita Putri (2023)
The prevalence of Type 2 Diabetes Melitus (T2DM) tend to climb and needed to be decreased, so management which is in terms of food selection. Food selection that do not quickly raise blood glucose levels with a low glycemic index (GI) or low glycemic load (BG) foods and high fiber such as tempeh with pumpkin seed substitution. The purpose of this study to analyze of the GI and BG made from pumpkin seeds and soybean. This study used a cross over trials 11 adult subjects. There were two groups the other one the control group was given glucose and the treatment group is pumpkin seed substitution contain 25 g carbohydrates. The results of the interventation blood glycemic mean of the treatment group was lower than the control group. The results of the ANOVA the AUC area of the control group was significantly different (p<0.05) compared the treatment group. The GI values of tempeh with pumpkin seed substitutions F0, F1, F2, F3 in order to get 16,80; 15,41; 12,84; 9,85, while the BG is 0,76; 0,70; 0,58; 0,45 included the low category. Consumption of foods with low GI and BG does not increase blood glycemic significantly, correlated for blood glucose controlled.